Enhancing cognitive and entrepreneurship competencies through EBL - Kholilah; Vega Wafaretta; Dian Syariati (Asian Journal of Accounting Research, 2019)
Entrepreneurship-based learning (EBL) is one of the student-center learningmethods that can answer learning challenges in the era of industrial revolution 4.0. EBL is expected to improve students’ competencies and make students more adaptable to the changes in the world of work in the future. The paper aims to discuss this issue.This study uses quasi-experiments and divides classes into project class and control class. The project consists of making business proposals, conducting business, liquidating the partnership, and recording business transaction using the Xero platform. The Wilcoxon Signed Ranks Test, Mann–Whitney Test and independent t-test were carried out to test whether there are differences of cognitive abilities and entrepreneurial (general, social and functional) competencies between the project class and control class.The results of the study shows there are differences of understanding of partnership accounting and the achievement of social and functional entrepreneurial competencies between the project class and control class.This study implies in using EBL to improve entrepreneurial skills for students beyond cognitive abilities.The novelty of this research is the implementation of EBL in partnership accounting topics.